Mediastinal Lymphoma in a Cat with Feline Leukemia Virus Mediastinal Lymphoma in a Cat with Feline Leukemia Virus - de Azevedo, Luana Baptista; Fenner, Bruna Bertin; Dalegrave, Suélen; Vedana, Camilla Federizzi; Toigo, Letícia Ângela Tomazzoni; Gauer, Natali Gabriela; de Oliveira, Eduardo Conceição (Acta Scientiae Veterinariae, 2022)
Background: Mediastinal lymphoma occurs at a high incidence in cats positive for feline leukemia virus (FeLV). It is a malignant lymphocytic neoplasm that may trigger clinical signs such as dyspnea, apathy, regurgitation, and weight loss. The objective of this work is to report a case of mediastinal lymphoma associated with FeLV in a cat, and describe the clinical, pathological, diagnostic, and therapeutic aspects that can help the diagnosis and treatment of this disease. Case: A 3-year-old male neutered cat weighing 4.6 kg, positive for FeLV, and with a history of dyspnea and hyporexia was referred to a private veterinary clinic in the city of Caxias do Sul, RS, Brazil. The only alteration found at the clinical examination was a muffled sound during lung auscultation. Radiographs of the thorax revealed the presence of pleural effusion; after drainage of the fluid, a mass located in the mediastinal area became radiographically observable. An analysis of the effusion fluid showed high cellularity characterized by a markedly pleomorphic population of individual round cells consistent with lymphocytes. Small lymphocytes with a high nucleus:cytoplasm ratio, round nucleus, condensed chromatin, and inconspicuous nucleoli were observed, along with medium and large lymphocytes. The medium and large lymphocytes were characterized by a variably increased nucleus:cytoplasm ratio and a scant to moderate cytoplasm exhibiting moderate to intense basophilia and, occasionally, vacuoles. The nuclei were round, idented, or irregular; most of them were located eccentrically and contained coarse to finely granular chromatin. Nucleoli varied from single to multiple, round to angular, and central to peripheral and prominent. Macronucleoli and marked anisonucleosis were also observed, as well as binucleated cells and rare multinucleated cells. The conclusion was that it was a case of neoplastic effusion caused by a lymphoma. After an appointment with an oncologist, a chemotherapy protocol was established. The treatment of choice was CHOP, a combination of cyclophosphamide (20 mg/kg orally), doxorubicin (1 mg/kg intravenously), vincristine (0.5 mg/m2 intravenously), and prednisolone with a regressive dose starting at 2 mg/kg. The patient underwent 4 rounds of chemotherapy, and received a maintenance treatment thereafter. The patient’s condition remained stable for 390 days without relevant clinical or hematological alterations. Discussion: The diagnosis of mediastinal lymphoma was established by associating clinical finings, laboratory exams, and radiographic findings. Exams of utmost importance to reach this diagnosis were the thoracic radiography, which revealed the presence of a mass in the thorax, and the cytopathological analysis of the effusion fluid, as round cell neoplasms are easily dissociated. Young cats are the group most affected by FeLV, and mediastinal lymphoma is considered the most prevalent type of lymphoma in this species. The most common clinical sign is dyspnea; however, other signs such as apathy, weight loss, regurgitation (due to pressure on the esophagus), and Horner’s syndrome (owing to pressure on the thoracic sympathetic innervation) may also occur. This disease is treated with chemotherapy, with CHOP frequently used as the chemotherapeutic protocol. The good therapeutic response for a longer time than the average estimated by studies on the prognostic of this disease indicates that a correct diagnosis along with an assertive approach and the cooperation of the tutor are essential in cases of mediastinal lymphoma. Keywords: cat, neoplasm, virus, mediastinum, effusion. Título: Linfoma mediastinal em gato cm vírus da leucemia felina Descritores: gato, neoplasia, vírus, mediastino, efusão.